DESCRIPTION OF TWO NEW SPECIES OF Crenicichla (TELEOSTEI: CICHLIDAE) FROM THE LOWER IGUAZÚ RIVER WITH A TAXONOMIC REAPPRAISAL OF C. iguassuensis, C. tesay AND C. yaha - Piálek, Lubomír; Dragová, Klára; Casciotta, Jorge; Almirón, Adriana; Říčan, Oldřich (Ciudad Autónoma de Buenos Aires, 2015)
Five species of Crenicichla have been recorded so far from the lower Iguazú River. Four of them are endemic (members of the C. mandelburgeri species complex from the C. lacustris group) and living in sympatry; the fifth species (C. lepidota) belongs to an Amazon/Orinoco-centered species group (C. saxatilis) and is only distantly related to the remaining species. The four sympatric species differ substantially in their head/teeth morphology and related utilization of the ecological niches, and represent all known ecomorphs within Crenicichla. Two of them, a gregarious small-mouthed picker/grazer C. tapii sp. n. and a large-mouthed thick-lipped cavity explorer/excavator C. tuca sp. n. are described here as new species. The piscivorous large-mouthed species C. iguassuensis represents the ancestral form of the genus. The fourth species is the small-mouthed picker/molluscivore C. tesay with a robust lower pharyngeal jaw with molariform teeth. Populations referred to in previous studies as C. yaha are reclassified as C. tesay; C. yaha is an endemic species of the neighboring Urugua-í stream known only from nine specimens because the species has not been collected since 1989 (when a dam was constructed on this stream). The taxonomic status of the populations referred to here as C. iguassuensis remain tentative because these form a separate clade in mtDNA analysis, reveal slight morphological differences, and have a wide distribution gap to the type locality with similar yet undescribed species in the intervening area.
Keywords: Areas of endemism; morphoecological diversification; La Plata River basin; Paraná; species flocks